The Feasibility and Efficacy of a Brief Integrative Treatment for Adults With Depression and/or Anxiety: A Randomized Controlled Trial - Adrian L. Lopresti PhD; Stephen J. Smith MA; Alexandra P. Metse PhD; Tiffany Foster MA; Peter D. Drummond PhD (SAGE Publishing, 2020)
The aim of this study was to investigate the efficacy and suitability of a brief integrative intervention, Personalized Integrative Therapy (PI Therapy), for the treatment of adult depression and/or anxiety. In this 6-week, 3-arm, parallel-group, randomized trial, PI Therapy delivered alone or with nutritional supplements (PI Therapy + Supps) was compared to cognitive behavior therapy (CBT) in 48 adults with depression and/or anxiety. All treatments were delivered as a 1-day workshop plus 6 weeks of reminder phone text messages to reinforce topics and skills covered in the workshop. Affective symptoms decreased significantly and to the same extent in all 3 conditions. At the end of treatment, 33% to 58% of participants reported levels of depressive symptoms in the normal range, and 50% to 58% reported nonclinical levels of anxiety. Compared to CBT and PI Therapy, PI Therapy + Supps was associated with significantly greater improvements in sleep quality. These findings suggest that a brief integrative intervention with or without supplements was comparable to CBT in reducing affective symptoms in adults with depression and/or anxiety. However, sleep quality improved only in the PI Therapy + Supps condition. These findings will require replication with a larger cohort.